Implementasi Game Edukatif Bernuansa Islami untuk Meningkatkan Minat Belajar Matematika Siswa SMP - Modi Pratama; Moh Restu Hoeruman (Journal of Information System and Education Development, 2026)
Many students still perceive mathematics as a difficult and uninteresting subject, which results in low learning motivation. One approach considered effective in addressing this issue is game-based learning, which can create an interactive, enjoyable, and meaningful learning environment. This study aims to describe the concept of game-based learning, its implementation in mathematics education, and its effects on increasing students’ interest and motivation, particularly through Islamic-themed educational games. This research employs a literature review method by analyzing theories, books, and previous studies.The findings show that the use of educational games not only enhances students’ active engagement and facilitates their understanding of mathematical concepts but also provides a more enjoyable learning experience. Previous studies confirm that educational games can increase learning interest by up to 70–80% and foster positive attitudes toward learning.Moreover, the integration of Islamic values within educational games has been proven to strengthen noble character development, such as honesty, responsibility, and patience.Therefore, Islamic-themed educational games can serve as a strategic alternative to improve the quality of mathematics learning, provided they are supported by proper planning and teachers’ readiness in implementing them